Pengaruh Strategi Integrasi Digital Marketing Gojek Terhadap Visibilitas dan Brand Awareness - Kelvin Kelvin; Stefhani Susanto; Melson Melson; Eryc Eryc (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Digital Marketing has become a marketing approach adopted by many companies, one of which is Gojek. This technology company that provides various services in the super app continues to compete with its competitors. This study aims to analyze the digital marketing approach taken by Gojek, namely from social media, influencer marketing, Search Engine Optimization (SEO), Search Engine Marketing (SEM) and email marketing. The study was conducted descriptively with secondary data obtained from trusted sources such as Gojek's annual report and social media. The findings obtained are that the implementation of this digital marketing affects customer engagement which then increases loyalty and relationships with customers.